FULFILLMENT OF RESTITUTION RIGHTS FOR CHILDREN AS VICTIMS OF TRAFFICKING CRIME (STUDY OF DECISION NUMBER 68/PID. SUS/2023/PN. TKN) - Bengi, Rizki Mah; Surya, Achmad (fakultas hukum universitas PGRI Semarang, 2024)
This research aims to see how the implementation of the right to restitution and legal protection for victims of crime, especially victims of trafficking in the form of restitution is regulated in Law Number 21 of 2007 concerning Trafficking in Persons (TPPO Law). The method used in this research is normative juridical, namely legal research conducted by examining secondary data, using a statutory approach (statue approach) and case approach.The results of the research on the fulfillment of restitution rights for children as victims of human trafficking crimes (Study of Decision Number 68/Pid.Sus/2023/PN Tkn) the victim's family refused to apply for the victim's child restitution rights, this was confirmed by a statement made by the victim's family stating that they did not request restitution rights for the victim's child. It can be concluded that the right to restitution for child victims has not been implemented according to law enforcement officials in Central Aceh district.